Technical Note: The effect of 2D excitation profile on T1 measurement accuracy using the variable flip angle method with an average flip angle assumption - Svedin, Bryant T.; Parker, Dennis L. (Medical physics (Lancaster), 2017)
Purpose To study the accuracy and precision of T1 estimates using the Variable Flip Angle (VFA) method in 2D and 3D acquisitions. Methods Excitation profiles were simulated using numerical implementation of the Bloch equations for Hamming‐windowed sinc excitation pulses with different time‐bandwidth products (TBP) of 2, 6, and 10 and for T1 values of 295 ms and 1045 ms. Experimental data were collected in 5° increments from 5° to 90° for the same T1 and TBP values. T1 was calculated for every combination of flip angle with and without a correction for B1 and slice profile variation. Calculations were also made for flat slice profile such as obtained in 3D acquisition. Monte Carlo simulations were performed to obtain T1 measurement uncertainty. Results VFA T1 measurements in 2D without correction can result in a 40–80% underestimation of true T1. Flip angle correction can reduce the underestimation, but results in accurate measurements of T1 only within a narrow band of flip angle combinations. The narrow band of accuracy increases with TBP, but remains too narrow for any practical range of T1 values or B1 variation. Simulated noisy VFA T1 measurements in 3D were accurate as long as the two angles chosen are on either side of the Ernst angle. Conclusions Accurate T1 estimates from VFA 2D acquisitions are possible, but only a narrow range of T1 values within a narrow range of flip angle combinations can be accurately calculated using a 2D slice. Unless a better flip angle correction method is used, these results demonstrate that accurate measurements of T1 in 2D cannot be obtained robustly enough for practical use and are more likely obtained by a thin slab 3D VFA acquisition than from multiple‐slice 2D acquisitions. VFA T1 measurements in 3D are accurate for wide ranges of flip angle combinations and T1 values.